MSK Ultrasound: A Powerful Tool for Evaluating and Diagnosing Pectoralis Major Injuries in Healthcare Practice - Robert C. Manske; Chris Wolfe; Phil Page; Michael Voight (North American Sports Medicine Institute, 2024)
Accurately diagnosing pectoralis major injuries, particularly in athletes, often presents a challenge for healthcare practitioners. Although pectoralis muscle injuries are relatively uncommon, the diagnosis of a tear may be overlooked without careful screening by a thorough physical examination of both the injured and uninjured sides. While magnetic resonance imaging (MRI) has traditionally held the gold standard, musculoskeletal ultrasound (MSKUS) has emerged as a viable alternative. This article delves into the power of MSKUS in evaluating and diagnosing pectoralis major injuries, highlighting its dynamic capabilities, real-time visualization, and cost-effectiveness in comparison to MRI. By equipping healthcare professionals with a thorough understanding of MSKUS's potential, this article aims to empower them to confidently diagnose and manage pectoralis major injuries, ultimately improving patient outcomes and facilitating a faster return to function.